Plasma irisin depletion under energy restriction is associated with improvements in lipid profile in metabolic syndrome patients. (7th January 2014) - de la Iglesia, Rocio; Lopez‐Legarrea, Patricia; Crujeiras, Ana B.; Pardo, Maria; Casanueva, Felipe F.; Zulet, Maria A.; Martinez, Jose A.
Summary Objective A recently discovered myokine, irisin, may have an important role in energy metabolism. This study aimed to evaluate the relationship between this hormone and the lipid profile of patients with metabolic syndrome (MetS) following a hypocaloric diet. Design Ninety‐three Caucasian adults (52 men/41 women) diagnosed with MetS followed an 8‐week‐long energy‐restricted programme (−30% of the energy requirements). Anthropometric measurements, biochemical markers and plasma irisin levels were analysed before and after the nutritional intervention. Results Global plasma irisin levels were significantly reduced at the end of the study (−72·0 ± 100·9 ng/ml, P < 0·001) accompanying the weight loss (−6·9%). The depletion of irisin significantly correlated with changes in some atherogenic‐related variables: total cholesterol (B = 0·106, P = 0·018), total cholesterol/high‐density lipoprotein cholesterol ratio (B = 0·002, P = 0·036), low‐density lipoprotein cholesterol (B = 0·085, P = 0·037) and apolipoprotein B (B = 0·052, P = 0·002), independently of changes in body weight. Conclusions An association between the reduction in plasma irisin levels and the depletion of important lipid metabolism biomarkers was observed in patients with MetS undergoing an energy‐restricted programme.